EFL Speaking Fluency through Authentic Oral Production - Lopez, Jairo Israel; Becerra, Andres Paredes; Ramirez-Avila, Maria Rossana (Journal of Foreign Language Teaching and Learning, 2021)
This article describes the development of speaking fluency through authentic oral production in a six-week action research study of a public high school in Guayaquil, Ecuador. The methodology included a pre-test and a post-test that measured quantitative aspects of student’s spoken fluency (speed, pauses, repetitions, and corrections), a survey with closed-ended questions that collected learners’ perspectives towards their own speaking fluency, and an interview that addressed students’ opinions towards the elements of this action research. Twenty-four students’ audio recordings were analyzed and the results indicated that there was a significant increase of students’ speaking fluency. Results also showed that student’s perspectives on the innovation were positive since it raised awareness of their mistakes, helped them feel more confident, and let them practice the target language with autonomy outside the school boundaries. However, some considered that time and the lack of equipment and technological skills were issues that made the activity look less pleasant. This paper affirms that authentic oral production, facilitated by vlogging, helps students develop speaking fluency. Other EFL teachers and professionals in this field who would like to improve the fluency of their students in their oral production may consider reading this paper.